PENGARUH KUALITAS PRODUK DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN BISKUIT OREO DI PEKANBARU - , Hj. Aida Nursanti, Haji Irwansyah , Sri Restuti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The level of competition in the business world in Indonesia is very tight because every company is always trying to be able to increase market share and reach new customers. This requires producers to be more sensitive, critical and reactive to existing changes, both political, socio-cultural and economic. Requirements that must be met by a company in order to achieve success in competition is trying to achieve the goal of creating and retaining customers. This study aims to analyze the effect of product quality and advertising on purchasing decisions and consumer satisfaction of oreo biscuits in Pekanbaru. This research was conducted on people who had seen Oreo advertisements and bought Oreo biscuits in Pekanbaru with the criteria of being at least 15 years. The number of samples taken as many as 126 respondents with nonprobability sampling technique , namely sampling techniques that do not provide equal opportunities for each element or member of the population selected to be the sample. Data collection was carried out by distributing questionnaires. The data analysis technique uses path analysis and multiple linear regression tests. Based on the results of the analysis it was found that Product Quality has a significant positive effect on Purchasing Decisions, Advertising has a significant positive effect on Purchase Decisions, Purchase Decisions have a significant positive effect on Consumer Satisfaction, Indirectly Product Quality through Purchasing Decisions does not have a significant effect on Consumer Satisfaction, and indirectly Direct Advertising through Purchasing Decisions has a significant influence on Consumer Satisfaction Keywords : Product Quality, Advertising, Purchase Decision, and Consumer Satisfaction